PERBANKAN SYARIAH: ANTARA IDEALISME DAN OPORTUNISME - S Sutrisno (University of Merdeka Malang, 2015)
There are two motives establishment of Islamic banks in Indonesia, first established with the aim to develop the Islamic financial institutions (idealistic group). Second, Islmaic banks founded because there is profitable business opportunities (opportunistic group). The purpose ofthis study was to examine whether there are differences in performance between the idealistic Islamic banking group with opportunistic group. Variables in this study arefinancing, banking risk and profitability of Islamic banking. The populationin this study wereall Islamic banks in Indonesia that divided into idealist goup and opportunist group. The results showed that financing by the opportunist group dominated by financing based on profit margin concept or trade concept, while the financing portion of idealist group provides the finiancing base on profit sharing concept. In terms of risk aspect, there is a significantdifference in liquidity risk (FDR) and operating risk (BOPO) between groups of idealists byopportunists, while the risk capital(CAR) and risk financing (NPF) the difference was notsignificant. From the aspect of profitability, there are significant differences between idealist group and opportunists group.